(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Women are generallyperceived as home makers with little to do with economy or commerce. The topicof women in entrepreneurship has been largely neglected both in society ingeneral and in the social sciences. Not only have women lower participation ratesin entrepreneurship than men but they also generally choose to start and managefirms in different industries than men tend to do. The transition fromhomemaker to sophisticated business woman is not that easy. But this picture ischanging. In Modern India, more and more women are taking up entrepreneurialactivity especially in micro, small and medium scale enterprises. Women acrossIndia are showing an interest to be economically independent. They are willingto be inspired by role models- such as Indra Nooyi, Chief Executive–Pepsi Co.or Ekta Kapoor, Creative Director-Balaji Telefilms. The Indian women are nomore treated as beautiful showpieces. They have carved a niche for themselvesin the male dominated world. Indian women well manage both burden of work inhousehold front and meeting the deadlines at the work place. Women Entrepreneurship plays a prime role in industrialdevelopment. India has always been a land of entrepreneurs and also occupied astrategic position in the Indian economy. Today the village and MSME unitsaccount for about 45% of the total industrial production, 30% of the countryexports and estimated to employ 96millions person in over 26 million unitsthroughout the country. The government of India has defined women entrepreneurshipbased on women participation in equity and employed of a business enterprise. Women participationas entrepreneurs in these enterprises is become an important issue which needto be considered. Govt. of India is taking many initiatives in this directionand for this shake they have launched various policies for the development ofwomen entrepreneurship in MSME.